Las estrategias metodológicas que utilizan las maestras parvularias y su incidencia en el desarrollo de las relaciones lógico-matemáticas de las niñas y niños de primer grado de la unidad educativa “Roberto Alfredo Arregui Chauvín”, de la provincia de Bolívar, cantón Guaranda. Período lectivo 2013-2014. Lineamientos alternativos - Patiño Rodríguez, Jenny Rocío (2015)
This thesis refers to: METHODOLOGICAL STRATEGIES USING THE ranging from pre TEACHING AND ITS IMPACT ON THE DEVELOPMENT OF MATH-LOGICAL RELATIONS OF THE CHILDREN OF FIRST DEGREE OF EDUCATION UNIT "ROBERTO ALFREDO ARREGUI Chauvin" PROVINCE BOLIVAR, CANTON GUARANDA. LECTIVO PERIOD 2013-2014. ALTERNATIVE GUIDELINES conducted according to the provisions of the Rules of Academic System of the National University of Loja. He was raised as General Objective: To analyze the incidence of Methodological Strategies in the Development of Logical-Mathematical Relations of children in first grade. The methods used for the preparation of this research work were: Scientific, Inductive-Deductive, Analytic-Synthetic, Descriptive and Statistical Model, the same as served efficiently helps to achieve the proposed goal. The techniques and instruments used were: a survey of teachers ranging from pre-First Grade Education Unit "Roberto Alfredo Arregui Chauvin" in the province of Bolivar, to determine whether use Methodological Strategies in Daily Work Session, and, Observation Checklist applied to the children of First Degree Education Unit "Roberto Alfredo Arregui Chauvin" in the province of Bolivar, to evaluate the development of the Logical-Mathematical Relations, the same will be supported in the components of the Hubs Learning in the Curriculum Structure. It is concluded that: 100% of teachers ranging from pre-surveyed indicate that the Methodological Strategies used in the classroom with the children in developing their school day allows you to associate sets, sorting objects, linking objects-events, differentiating elements a set, solve problems, recognize and name objects; and 67% can match and measure and understand and remember stories. The Observing Guide to the children from first grade to assess the development of Logical-Mathematical Relations, the results determine that: 56% of girls and boys has observed Developing Logical-Mathematical Relations equivalent to very satisfactory, 40% and 4% satisfactory unsatisfactory